2010
DOI: 10.1177/0898264310361627
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Health and Education as Sources of Individual Variability in Cognitive Aging Among African Americans

Abstract: These findings suggest that although self-reported cardiovascular health contributes to variability in late life cognition in African Americans, education is a more universal predictor that should be further examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Other possible reasons for the race differences in unprompted performance include health status, specifically cardiovascular health, which predicts cognitive performance in older African Americans (Morgan et al, 2010). Given the increased prevalence of cardiovascular disease in African Americans relative to Whites (Go et al, 2014), it is possible that African Americans are experiencing a greater cognitive burden as a result of these risk factors (Kuo et al, 2005; Warsch et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible reasons for the race differences in unprompted performance include health status, specifically cardiovascular health, which predicts cognitive performance in older African Americans (Morgan et al, 2010). Given the increased prevalence of cardiovascular disease in African Americans relative to Whites (Go et al, 2014), it is possible that African Americans are experiencing a greater cognitive burden as a result of these risk factors (Kuo et al, 2005; Warsch et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Manly, Jacobs, Touradji, Small, and Stern (2002) found that race differences on a variety of neuropsychological measures were attenuated when literacy level (as a measure of educational quality) was included as a covariate. Health factors, especially cardiovascular factors, have also been implicated as possible mechanisms for race differences in cognition (Morgan, Sims, & Whitfield, 2010; Harper & Alexander, 1990), particularly given evidence that African Americans have a higher prevalence of hypertension and other cardiovascular issues (Go et al, 2014). Cardiovascular risk factors do appear to be important predictors of cognitive functioning in both African Americans and White older adults (e.g., Beeri, Ravona-Springer, Silverman, & Haroutunian, 2009; Izquierdo-Porrera & Waldstein, 2002; Warsch et al, 2013; Yaffe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Age appears to be a critical variable in these findings and assumes a significant proportion of the individual variability in this relationship. Also, demographic covariates, such as education, have previously been studied in this population and found to be important factors for which to account in examining cognitive functioning (Aiken Morgan et al, 2010; Whitfield, Allaire, Belue, & Ewards, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Typically and logically, factors such as health and education have been used to attempt to decompose the variability observed in cognitive functioning in African Americans (Aiken Morgan, et al, 2010), and future work in the area of personality and cognition in African Americans should also examine the role of health. Health and education are influenced by individual decisions as well as macro-social-contextual factors like insurance companies and local government policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation